STRENGTH OF BASALT FIBER CONCRETES - Shokhrukh Davlyatov; Solijonov Foziljon Sodiqjon ugli (Journals Park Publishing, 2024)
This article describes the results of experimental research on basalt fiber-reinforced concrete and the experimental studies conducted. It also presents conclusions on the strength and fracture toughness of basalt fiber-reinforced concrete.
Keywords: Basalt, fiber, strength, fracture toughness, concrete, cube, fiber concrete, press.